Full House : Junge Britische Kunst. (Wolfsburg : Kunstmuseum Wolfsburg, 1996)
Billingham, Richard ; Borland, Christine ; Bulloch, Angela ; Chapman, Dinos & Jake ; Collishaw, Mat ; Emin, Tracey ; Fairhurst, Angus ; Gordon, Douglas ; Hume, Gary ; Lane, Abigail ; Lucas, Sarah ; McQueen, Steve ; Pippin, Steven John ; Starr, Georgina ; Wearing, Gillian ; Wilson, Jane & Louise ; Taylor-Wood, Sam
biografie
Full House : Junge Britische Kunst / Young British Art, Kunstmuseum Wolfsburg, 14. Dezember 1996 - 31. März 1997
kunstcatalogus
Keywords: Groot-Brittannië